LIMB SALVAGE IN A NON-REVASCULARIZABLE DIABETIC FOOT USING MESENCHYMAL STEM CELLS AND HYPERBARIC OXYGEN THERAPY: A CASE REPORT (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetic foot ulcers (DFUs) associated with chronic limb-threatening ischemia (CLTI) significantly increase the risk of major amputation, especially in patients unsuitable for revascularization. In such cases, alternative limb salvage strategies are essential. Case Presentation: A 75-year-old male with type 2 diabetes mellitus, hypertension, and coronary artery disease presented with a 6-month history of non-healing, infected wounds at the amputation stumps of the left first, second, and third toes. Clinical examination revealed chronic ulceration with poor perfusion. Imaging demonstrated diffuse infrapopliteal arterial disease with poor distal runoff, and the limb was deemed non-revascularizable. Intervention: The patient underwent staged surgical debridement to remove necrotic tissue and reduce infection. This was followed by a multimodal adjunctive approach including intramuscular administration of allogeneic bone marrow-derived mesenchymal stem cells (MSCs), serial applications of platelet-rich fibrin matrix (PRFM), and 19 sessions of hyperbaric oxygen therapy (HBOT). Supportive management included culture-directed antibiotics, glycaemic optimization, nutritional support, and offloading. Outcome: The patient showed progressive wound healing with formation of healthy granulation tissue. Complete epithelialization was achieved by 12 weeks, and major limb amputation was avoided. No significant adverse events were observed during treatment or follow-up. Conclusion: A multidisciplinary approach combining surgical debridement, mesenchymal stem cell (MSC) therapy, platelet-rich fibrin matrix (PRFM), and hyperbaric oxygen therapy (HBOT) may facilitate limb salvage and enhance wound healing in selected patients with non-revascularize diabetic foot ulcers. Mesenchymal stem cells, through their angiogenic, immunomodulatory, and regenerative properties, may play a significant role in improving tissue repair and avoiding major amputation in complex ischemic diabetic foot wounds. Further studies are required to validate efficacy and establish standardized treatment protocols.